Keanekaragaman Bakteri Di Sumber Mata Air Science Techno Park Desa Taloetan Kecamatan Nekamese - Manansang, Tesalonika; Stanis, Stefanus; Mamulak, Yulita Iryani (Universitas PGRI Adi Buana Surabaya, 2024)
Bacteria play an important role as bioindicators of water quality and also play a role in the ecological cycle that helps degrade organic materials in spring sources. The spring is one of the springs located in the development site of Science Techno Park Widya Mandira Catholic University located in Taloetan Village, Nekamese District, Kupang Regency. This study aims to determine what bacteria, dominant bacteria, and characters contained in the source of Science Techno Park springs in Taloetan Village, Sub-District. The stages in this study are as follows: 1. Isolation of bacteria from spring water sources 2. Bacterial purification and 3. Characterization of bacteria 4. Identification of bacteria is by matching the characters tested with Bergey's Manual of Determinative Bacteriology 9th. The results showed that sourced from two sampling points obtained as many as 20 bacterial isolates. at point one as many as nine isolates namely isolates and colon as many as eleven isolates namely BA 1.1, BA 1.2, BA 1.3, BA 1.3, BA 1.4, BA 1.7, BA 1.8, BA 1.9, BA 1.10, BA 2.1, BA 2.2, BA 2.3, BA 2.3, BA 2.4, BA 2.5, BA 2.6, BA 2.7, BA 2.8, BA 2.9, and BA 2.10. The conclusion of this study is that 20 bacterial isolates from samples of Science Techno Park springs in Taloetan village, nekamese have similarities with 13 genera, namely acidomonas, acinetobacter, microbacterium, bordetella, brucella, salmonella, xanthobacter, marinomonas, aeromonas, escherichia, spirillum, azotobacter, flavobacterium., the dominant genus in the springs of Science Techno Park in Taloetan Village, Nekamese District, namely the genus Acidomonas and the genus Salmonella, and the characteristics of bacteria in general are bacil, all bacterial isolates can ferment types of glucose sugar, all bacteria can’t grow at temperatures of 50ºC, cannot grow at pH 3, and cannot grow at NaCl 10% & 15%. Keywords: bacteria, spring source, isolation, characterization, and identification